Centralization and Decentralization of Zakat Management in Lontara' Sukku'na Wajo, South Sulawesi: Philological Approach - Ilyas, Musyfikah; Ilyas, Husnul Fahimah; Arafah, Sitti; Idris, As. Rakhmad; Bahri, Saeful (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2025)
This article aims to examine the centralization and decentralization of the zakat management system at Lontara Sukku'na Wajo.. The research method used in this article is based on the Lontara’ Sukkuna Wajo (LSW) manuscript as the primary data source. This manuscript describes religious practices, especially zakat management system in the past. The data were studied using a philological approach through these methods: transliteration, translation, and interpretation of text and context related to zakat, then relating them to the present. This research found that there are relevances between LSW manuscripts and religious practices that developed in the community in the past and present, especially regarding the centralization and decentralization of zakat management. The centralization system of zakat management in LSW is marked by the absence of Friday prayers in the area and the incompleteness of Sara’ officials so the zakat management system must be centralized and follow the areas with complete Sara’ equipment, so they must pay their zakat in the Wajo Kingdom. Meanwhile, the decentralization system of zakat management can be implemented if the community order in the region is complete, marked by the holding of Friday prayers and complete Paréwa Sara’ (officials in charge of handling religious matters). The Paréwa Sara’ consists of Kali, Katte’, Amele’ (or an amil), Pangulu Limpo, and Bilala. Friday prayers and the completion of the Paréwa Sara’ became a measure in establishing a legal product at that time. A well-established region was considered capable of managing itself. If it is manifested in the present condition, then zakat management institutions or organizations that have been accredited in their fields are considered capable of managing their own zakat assets under their authority.